A Study of Medication Adherence and Medication Compliance to Insulin Therapy in Type I and Type II Diabetic Patients - P R, Anju; Siddiq, Abubaker (Indian Journal of Pharmacy Practice)
Non-adherence to treatment is an important and often unrecognized risk factor that contributes to reduced control of blood sugar hence this study aims at assessing the level of medication adherence and compliance to insulin in diabetic patients. It also determines to investigate factors affecting non adherence to insulin and to improve the patient’s knowledge towards their disease and medication. Objectives: To assess the medication adherence and compliance to insulin in Type I and Type II diabetic patients and to find out the factors affecting non adherence to insulin. Materials and Methods: This was a prospective observational study which was carried out for a period of six months at General Medicine in-patient Department of Basaveshwara Medical College and Hospital and Chitradurga Diabetic Centre, Chitradurga. Results: A total of 101 patients enrolled in the study of both type of diabetes mellitus and the data was collected in General medicine department. In which 7 patients were dropped from the study. Human Actrapid, Human Mixtard and Insugen are the main analogues of insulin prepatations used for the treatment. 81% of the patients has administered insulin subcutaneously. Most common comorbidity observed in diabetic population is hypertension. The Morisky medication adherence Scale (MMAS-8) results showed the P value was 0.000*. Inconvenience is the main factor which affected for Non-adherence to the treatment. Conclusion: In conclusion it is evident from our study that 82% of the population was adherent to insulin and 81% of the population was compliant after follow up.
Keywords: Insulin; Medication Adherence; Human Actrapid; Prospective.